Shopping as Fun, Function, and Tradition: A Study of The Influence of Hedonic, Utilitary, and Shopping Culture on Impulse Buying in The Era of Consumerism - Irdiana, Sukma; Budiyanto, Budiyanto; Suhermin, Suhermin (Journal of Social Science and Business Studies, 2025)
The purpose of this study is to determine the influence of hedonic shopping motive, utilitarian shopping motive and cultural shopping motive on Impulse Buying in the era of consumerism so that it can later become a reference in the world of e-commerce. The study was conducted throughout Indonesia with a sample of 80 respondents. The variables used in this study include hedonic shopping motive, utilitarian shopping motive and cultural shopping motive as independent variables or free variables and Impulse Buying as the dependent variable or dependent variable. The data used in this study are primary data, obtained from the results of respondents' answers collected with the help of a questionnaire. The sampling method uses a non-probability sampling technique used in this study, namely the purposive sampling technique, a technique for determining samples with certain considerations. The analytical methods used in this study are validity testing, reliability testing, analysis stages using Multiple Linear Regression and hypothesis testing. With the help of the SPSS 25 program for windows. The results of this study indicate that the hedonic shopping motive variable has no significant influence on impulse buying, while the utilitarian shopping motive and cultural shopping motive have a significant influence on impulse buying in the consumerism era, either partially or simultaneously.